Growth and essential oil content of accessions of Lippia rotundifolia in Minas Gerais, Brazil - Meira, Messulan Rodrigues; Martins, Ernane Ronie; Silva, Julio Cesar Rodrigues Lopes [UNESP]; Azevedo, Brayonn Mascarenhas (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the growth and essential oil content after transplantation and cutting of Lippia rotundifolia accessions from a natural population from the state of Minas Gerais, Brazil. Eight accessions were evaluated (PVP, GIG, RPE, ODA, JFE, PRP, SGS, and RTI) in six periods (60, 81, 102, 123, 144, and 165 days after transplanting and cutting), in a completely randomized experimental design. The following parameters were assessed: average width and length of the basal, median, and apical pair of leaves; plant height; stem diameter; and number of leaves. At 165 days, the yield of essential oil and the fresh and dry phytomass of the aerial part were also evaluated. Sixty days after the last evaluation, regrowth was measured from height, stem diameter, and number of leaves. The JFE accession stands out for emission of leaves, with a better development at 165 days after transplanting. RPE and PRP respond well to regrowth at 102 and 123 days after cutting, respectively. The SGS accession shows a high essential oil yield of 2.2%, and PVP, a low yield of 0.3%.
Crescimento e teor de óleo essencial de acessos de Lippia rotundifolia em Minas Gerais, Brasil
Keywords: Agronomic behavior; Germplasm; Medicinal plant; Rosemary